26. DEVELOPMENT OF A METHOD FOR PREPARING STANDARDIZED DRY EXTRACT OF QUERCETIN FROM THE MEDICINAL HERBS MURDANNIA NUDIFLORA (L.) BRENAN (Vietnam Journal of Community Medicine, 2025)
Objective: To develop a standardized method for preparing a dried extract from Murdannia nudiflora (L.) Brenan.Methods: The dried extract was prepared from a liquid crude extract and evaluated for quality parameters according to the Vietnamese Pharmacopoeia V.Results: The obtained extract had a moisture content of ~25%, which was then mixed with cassava starch (25%) and statically dried at 90°C for 8 hours. The final product exhibited the following characteristics: dry, loose, homogeneous powder with a dark brown color, hygroscopicity, a characteristic herbal odor, no fungal contamination, and a sweet taste. Quality control tests confirmed: loss on drying ≤ 5%, fineness: ≥ 90% of particles passed through a 355 µm sieve. Thin-layer chromatography: distinct and uniform spots with Rf values matching those of the reference standard and test samples. HPLC analysis: A clear quercetin peak with 99.19% purity compared to the standard. Quercetin content ≥ 80 mg/g in the dried extract.Conclusion: A standardized dried extract of Murdannia nudiflora was successfully prepared, containing a minimum of 80 mg/g quercetin (on a dry weight basis). These findings provide a scientific foundation for further research and development.
Keywords: Preparation, dried extract, quercetin, Murdannia nudiflora.